“The facts alone will not save us”: A workshop on speculative education future and history making - Costello, Eamon; Hrastinski, Stefan; Veletsianos, George; Macgilchrist , Felicitas (Proceedings of the International Conference on Networked Learning, 2024)
This workshop aims to explore speculative fiction as a form of educational enquiry and practice. In this pursuit it draws upon the provocative contention of Ruha Benjamin (2016) that “the facts, alone, will not save us.” Instead, she argues, “social change requires novel fictions that reimagine and rework all that is taken for granted about the current structure of society. Such narratives are not meant to convince others of what is, but to expand our own visions of what is possible” (Benjamin, 2016). The ethical implications of educational technologies (EdTech) from simple classroom tools to almighty platforms are raising increasing concerns. These are postdigital concerns insofar as they are inescapable yet also emergent and ongoing. They are amplified by the power and influence of AI (Bozkurt et al, 2023; Cox et al 2023) with its implications for fraud, scams, surveillance, privacy and more fundamentally encodings of privileged norms of race, gender, sexuality, religion and so on. In addition the material and carbon costs of digital learning may force us to reckon with EdTech as inherently ecologically destructive (Selwyn, 2021). Is this to say that all our futures are grim and that hope has been foreclosed? Or if not, how can we work together to plot our way out of these problems? Indeed, would trying to solve all of this too quickly be part of the problem and start another round of techno-solutionism? One approach that has seen increasing attention is the use of storytelling as a sense-making activity that may allow us to first “stay with the trouble” (Harraway, 2020) and describe it, before rushing to the fix. This recent speculative turn has seen educational researchers attempt to cast themselves as writers of fictions that can explore the multitude of interrelated socio-technical issues that are characteristic of complex contemporary networked learning environments (Houlden & Veletsianos, 2023; Hrastinski, 2023; Selwyn et al., 2020; Macgilchrist et al., 2020). It has seen teachers and educators developing or adopting speculative scenarios as tools for students to explore the types of socio-technical entanglements that our world now involves (Krutka et al., 2022). In this workshop participants will co-create speculative fictions that explore hopeful and dystopic possibilities of education. Participants will explore the development of educational fictions based on speculative futuring, of no-yet-ness (Ross, 2017), but also alternative histories that might allow us see the prospective tools of our work, including texts, as neither neutral nor ahistorical. The concept of anti-patterns and deliberately destructive design will be introduced to allow participants to pull on conceptual threads that help unravel education as a relentless and progressive assembly and instead see it as a story that may be unlearned and retold. In summary this workshop provides an invitation to participants to use their deep imaginative capabilities to dream new educational interfaces, via speculative fiction, that allow us to be more awake and alive to ourselves, our students and the communities we serve.